PEBBLES IN THE TEACHER’S SHOES: PORTRAITS AND CHALLENGES OF RELIGIOUS MODERATION OF ISLAMIC RELIGIOUS EDUCATION TEACHERS - Adhan, Syamsurijal (Al-Qalam, 2021)
The Islamic Religious Education (PAI) Teacher is one of the educators who is considered to have an important role in shaping students' religious understanding. Of course, the understanding of religion expected to emerge from these PAI teachers is a moderate one that is not extreme and does not exaggerate in expressing certain religious views. However, in some cases, it was found that PAI teachers were intolerant and even approved of radical actions in the name of religion. This qualitative research method aims to describe the portrait as well as the challenge of moderation for Islamic Religious Teachers, especially those in Madrasah Aliyah and Sekolah Menengah Umum (SMU). This research was conducted in two regions in South Sulawesi, Bulukumba and Makassar. The results showed that some Islamic education teachers still have problems in their views and attitudes of religious moderation, especially in their acceptance of diversity. Regarding nationalism, there are still several obstacles, for example, PAI teachers who prohibit flag ceremonies. But on the other hand, the religious moderation of the PAI teachers shows a lot of hope. There are still many PAI teachers who have a good religious perspective and attitude. Some PAI teachers affiliated with certain religious groups have puritanical and exclusive view. Still, in certain matters, such as the acceptance of the Republic of Indonesia, they are starting to be moderate. The right approach and intervention will be able to overcome the obstacle of intolerance among Islamic Education Teachers